2019
DOI: 10.1007/s40641-019-00126-x
|View full text |Cite
|
Sign up to set email alerts
|

Boundary Layer Clouds and Convection over Subtropical Oceans in our Current and in a Warmer Climate

Abstract: Purpose of ReviewWe review our understanding of mechanisms underlying the response of (sub)tropical clouds to global warming, highlight mechanisms that challenge our understanding, and discuss simulation strategies that tackle them. Recent Findings Turbulence-resolving models and emergent constraints provide probable evidence, supported by theoretical understanding, that the cooling cloud radiative effect (CRE) of low clouds weakens with warming: a positive low-cloud feedback. Nevertheless, an uncertainty in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
57
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(62 citation statements)
references
References 113 publications
(119 reference statements)
4
57
0
1
Order By: Relevance
“…Provided the identified resolution-dependence of the cloud cover feedback carries over to other model codes, then it implies that storm resolving models may exaggerate trade wind cumulus cloud feedback. It is also interesting to compare with earlier studies, where LES simulations previously have suggested trade wind cumulus feedback in the range 0.3 and 2.3 Wm −2 K −1 (Bretherton, 2015;Nuijens and Siebesma, 2019), and observational studies up until recently likewise 0.3 -1.7 Wm −2 K −1 (Klein et al, 2017). A recent observational study, however, finds a near-zero trade wind cumulus cloud feedback (Myers et al, submitted), which is in line with our results.…”
Section: Discussionmentioning
confidence: 56%
“…Provided the identified resolution-dependence of the cloud cover feedback carries over to other model codes, then it implies that storm resolving models may exaggerate trade wind cumulus cloud feedback. It is also interesting to compare with earlier studies, where LES simulations previously have suggested trade wind cumulus feedback in the range 0.3 and 2.3 Wm −2 K −1 (Bretherton, 2015;Nuijens and Siebesma, 2019), and observational studies up until recently likewise 0.3 -1.7 Wm −2 K −1 (Klein et al, 2017). A recent observational study, however, finds a near-zero trade wind cumulus cloud feedback (Myers et al, submitted), which is in line with our results.…”
Section: Discussionmentioning
confidence: 56%
“…In contrast, lidars have the potential to detect them much better (Liou and Schotland, 1971;Spinhirne et al, 1982). Space-borne lidars associated with missions such as LITE (Lidar In-space Technology Experiment, Winker et al, 1996), GLASS (Geoscience Laser Altimeter System; Palm et al, 2005;, CALIPSO (Cloud-Aerosol LIdar with Orthogonal Polarization; Winker et al, 2003) or more recently CATS (Cloud-Aerosol Transport System, Yorks et al, 2016) have even revolutionized our knowledge of the global distribution of clouds (Berthier et al, 2008). However, cloud observations from ground-based, airborne or satellite lidar technology were made at the nadir or zenith.…”
Section: Introductionmentioning
confidence: 99%
“…They showed that shallow convection becomes more vigorous and transports more water vapor from the boundary layer to a free atmosphere in a warmer climate for models in which the shallow convection scheme is active. Brient and Recent studies based on observational relationships and GCMs also tend to support decreases in low cloud cover in warmer climates and the positive low cloud feedback (e.g., Klein et al 2017, Nuijens andSiebesma 2019). It is shown that decrease in low cloud cover in warmer climates is plausible based on CMIP5 multi-model simulation data (Qu et al 2014(Qu et al , 2015 and observational relationships (e.g.…”
Section: Various Studies Related To Future Changes In Mlcsmentioning
confidence: 89%
“…All of these processes affect the vertical profile of the cloud-topped boundary layer. Various physical processes that control MLCs and their complicated interactions are discussed in more detail in some review papers (e.g., Wood 2012, Nuijens andSiebesma 2019).…”
Section: Mechanisms For the Formation And Maintenance Of Mlcsmentioning
confidence: 99%